Kajian Kebugaran Wanita dari Aspek Kecukupan Gizi, Status Gizi dan Aktivitas - Sugiarsi, Sri (Universitas Muhammadiyah Surakarta, 2013)
The level of fitness can be reached by having good nutrition, doing exercise and spending sometimes for sleeping sufficienly. Purpose of this study was to examine the relationship between nutritionalintake, nutritional status, adequate sleep and exercise in women?s fitness in the Taurus gymnasiumCenter of Surabaya. Respondents of this research were 60 members of Taurus gymnasium. This wascross sectional analytical study to show the influence of variables of the sufficiency of nutrition (calory,carbohydrate, protein, vitamin B1, fat, calcium), nutritional status and activity and the level of fitness.Theresult of the statistical test with =0,05 showed that there is a significant relationship between sufficiencyof iron element and frequency of exercise and the level of fitness. It is sugested for members of Taurusgymnasium Center to do exercise regulary and improve eating pattern by consuming various menu, muchmore non heme protein than heme protein, and consuming vitamin C sufficienly